A QUALITATIVE ANALYSIS OF USER INTERFACE DESIGN ON A SHARIA FINTECHAPPLICATION BASED ON TECHNOLOGY ACCEPTANCE MODEL (TAM) - Azhar Alam; Ilham Aji Saputro (LPPM STMIK Pringsewu, 2022)
This research aims to discuss user interface design analysis on the use of Sharia applications based on the technology acceptance model and sharia principles. This research wants to illustrate the assessment results of the initial view and know-how easy to use in a Sharia fintech application, namely Sharia funds. This study interviewed ten respondents from young and old, both young and old, who had not used this application or who were already using it. This study uses a type of qualitative research with the Grounded Theory method to explain the phenomenon specifically. The results showed that the User Interface in Dana Syariah application, which is assessed in terms of Consistency, Personality, Layout, and control and affordances, could be said almost all views make it easy for users young and old. However, there are some drawbacks, perhaps due to less innovative colors. There are few constraints found for older and above average users who find it difficult to distinguish some of that application's particular functions. This research recommends Islamic fintech application providers to pay better attention to the user interface while inviting academics in Sharia economics to evaluate fintech applications' use to develop a faster Islamic economy.